Standardization of Rhizome Simplicia from the Zingiberaceae Family in Terms of Methods and Quality: A Review - Silalahi, Yosy Cinthya Eriwaty; Surbakti, Christica Ilsana; Suharyanisa, Suharyanisa; Suryani, Monica; Ulfata, Zikri; Panjaitan, Grace Emmas Sondang; Marbun, Eva Diansari (NSMRJ: Nusantara Scientific Medical Research Journal, 2025)
Simplicia rhizomes from the Zingiberaceae family are important raw materials in the traditional medicine industry, as they contain bioactive compounds such as flavonoids, alkaloids, and tannins. The quality of simplicia is strongly influenced by post-harvest processing methods, particularly drying. This study aims to systematically review the quality of Zingiberaceae rhizome simplicia based on ten national scientific journals published between 2015 and 2024. The method employed was a literature study using a qualitative descriptive approach, evaluating specific quality parameters (organoleptic characteristics, solubility, and phytochemical tests) and non-specific parameters (moisture content, ash content, and microbial contamination) according to the Indonesian Herbal Pharmacopoeia. The results indicate that oven drying at 50–60 °C for 24–48 hours produces the best-quality simplicia, characterized by moisture content below 10%, ash content within acceptable limits, and high flavonoid levels. Other drying methods, such as sun drying and natural air drying, showed more variable outcomes and in some cases exceeded standard limits, particularly in acid-insoluble ash levels and microbial contamination. Several simplicia samples obtained from traditional markets did not meet quality standards due to suboptimal washing and storage processes. This study concludes that simplicia quality standardization must comprehensively address technical stages from washing to drying. The use of extracts is more strongly recommended than raw simplicia to ensure consistency, stability, and safety of herbal products. Strict quality standards are essential to support the effectiveness of traditional medicines derived from Zingiberaceae.